Viral Response to Specifically Targeted Antiviral Therapy for Hepatitis C and the Implications for Treatment Success - Curtis L Cooper (Canadian Journal of Gastroenterology)
Currently, hepatitis C virus (HCV) antiviral therapy is characterized by long duration, a multitude of side effects, difficult administration and suboptimal success; clearly, alternatives are needed. Collectively, specifically targeted antiviral therapy for HCV (STAT-C) molecules achieve rapid viral suppression and very high rapid virological response rates, and improve sustained virological response rates. The attrition rate of agents within this class has been high due to various toxicities. Regardless, several STAT-C molecules are poised to become the standard of care for HCV treatment in the foreseeable future. Optimism must be tempered with concerns related to the rapid development of drug resistance with resulting HCV rebound. Strategies including induction dosing with interferon and ribavirin, use of combination high-potency STAT-C molecules and an intensive emphasis on adherence to HCV antiviral therapy will be critical to the success of this promising advance in HCV therapy.